The Relationship Between Exclusive Breastfeeding to the Emotional Development of Children in Lubuk Barumun District, Padang Lawas Regency - Kumala Sari Rambe; Rina Marlina Hutasuhut (International Journal of Public Health Excellence (IJPHE), 2023)
Breast milk is a complex biological fluid which contains all the nutrients that are useful for the physical growth and development of infants in meeting the needs of foster care (physics-biomedical), compassion (needs for affection/emotions, and sharpening (the need for stimulation). Exclusive breastfeeding is the provision of breast milk to babies from birth to 6 months of age without the addition of other food/drinks. The research method uses observational analytic research methods. Analytical research is research that tries to explore how and why health phenomena occur, then analyzes the dynamics of the correlation between phenomena, namely risk factors and effect factors with a cross-sectional approach by examining the effect of breastfeeding. The results of this study are by using Chi-Square p-value = 0.017 there is a relationship between exclusive breastfeeding and emotional development in toddlers. Conclusion There is a significant relationship between exclusive breastfeeding and emotional development in toddlers with a p-value of 0.017. The proportion of normal emotional development in toddlers is 62.5% while those that are not normal are 37.5%